Social Media and Sales Performance in B2B Markets: Insights from a Dual Approach to Performance Measurement - Prasetya, Prita; Najib, Mukhamad; Soetjipto, Budi Eko (Universitas Brawijaya, Indonesia, 2025)
The strategic significance and application of social media in diverse business contexts have been extensively covered in recent academic and practitioner literature. This study uses a dual measurement approach for relative and absolute performance to investigate how social media use affects sales force performance in business-to-business (B2B) settings. It focuses on the mediating roles of relationship quality and brand awareness. Data was gathered from 206 Indonesian B2B salespeople using a quantitative survey method. Purposive sampling was used to distribute a structured questionnaire to gather data. The data was analyzed using AMOS software and Structural Equation Modeling (SEM). The findings demonstrate that social media use enhances sales performance by positively impacting relationship quality, relationship strength, and brand awareness. Social media contributes to increased customer interaction, commitment, and trust, all of which improve relative and absolute performance. In this relationship, the strength and quality of the relationship act as mediators. Compared to the path involving brand awareness, the mediation path through relationship strength and quality is more effective in enhancing sales performance. This finding adds to the studies on social media use in business-to-business settings. Nevertheless, the sample is restricted to a single nation and sector. Subsequent studies could expand the sample to encompass additional industries and geographical regions. The study benefits B2B managers by promoting more active social media use among salespeople and highlighting the importance of developing social media competency, as well as providing training to enhance sales performance.